PSIX-21 Performance and health of dairy calves fed with acidified milk in tropical climates - Coelho, Marina (J Anim Sci, 2020)
The acidification of milk is used in mild climate countries as a way of conservation because it reduces the feed bacteriological load and consequently improves the animals’ performance. However, this management is hampered in hot climates. Thirty-tree males and female Holstein colostrum-fed newborn calves were used in a randomized block experimental design and fed different liquid feed: refrigerated whole milk (WM); acidified milk kept in room temperature (AM); or a commercial milk replacer (MR: 22.9% CP; 18.8% fat; 16% solids). The animals were housed in individual shelters with free access to water and starter concentrate since 2d of age. Calves were fed 6L of liquid diet divided in two meals until their gradual weaning at 56d of age. The milk was acidified to a pH of 4.5 with formic acid 12 hours prior to feeding and kept in ambient temperature (23.7°C). The pH was monitored and corrected to the target pH before each meal. Blood samples were weekly collected and health was evaluated daily. No effect on feed intake was observed (Table 1). Feeding AM decreased calves’ weight gain as compared to that for WM fed calves but with no difference from those fed MR. Fecal scores was higher for MR as compared to WM fed calves, but with no difference from AM. However, AM calves presented higher average rectal temperature than WM fed calves, but a lower number of days with fever. AM is an alternative for feeding calves in tropical climates with performance similar to that observed for MR but with lower days with fever. [Image: see text]